2018
DOI: 10.1371/journal.pone.0202273
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae size refuge from herbivory promotes alternative stable states on coral reefs

Abstract: Coral reef systems can undergo rapid transitions from coral-dominated to macroalgae-dominated states following disturbances, and models indicate that these may sometimes represent shifts between alternative stable states. While several mechanisms may lead to alternate stable states on coral reefs, only a few have been investigated theoretically. We explore a model that illustrates that reduced vulnerability of macroalgae to herbivory as macroalgae grow and mature could be an important mechanism: when macroalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 40 publications
(59 reference statements)
6
47
0
Order By: Relevance
“…Note that N is consistently enriched at the fringing reef sites relative to the back reef and reef crest. Also note that LTER sites 1, 2, and 3 tend to be enriched relative to sites 4, 5, and 6. et al 2017, Briggs et al 2018). In this study, we found that several species of macroalgae have recently increased in abundance on back reef habitats of Moorea, but only where levels of N are relatively high.…”
Section: Anthropogenic Nitrogen Sourcessupporting
confidence: 59%
See 1 more Smart Citation
“…Note that N is consistently enriched at the fringing reef sites relative to the back reef and reef crest. Also note that LTER sites 1, 2, and 3 tend to be enriched relative to sites 4, 5, and 6. et al 2017, Briggs et al 2018). In this study, we found that several species of macroalgae have recently increased in abundance on back reef habitats of Moorea, but only where levels of N are relatively high.…”
Section: Anthropogenic Nitrogen Sourcessupporting
confidence: 59%
“…Nutrient enrichment can allow for the proliferation of algae that are physiologically unable to grow under nutrient poor conditions. In addition, excess nutrients can also facilitate algae indirectly through the loss of top‐down control if adding nutrients causes algal production to outpace herbivory (Scheffer et al 2008, Arias‐González et al 2017, Briggs et al 2018). In this study, we found that several species of macroalgae have recently increased in abundance on back reef habitats of Moorea, but only where levels of N are relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…may similarly reduce propagule survival through grazing of the EAM even though detrital aggregates may be the primary dietary target (Wilson 2000, Brandl et al 2018. Although our results suggest that cryptobenthic blennies contribute to the mortality of small Sargassum propagules (<2 mm, and up to 25 days post-settlement), it is likely that Microhabitats enhance propagule survival Sargassum and other macroalgal propagules will quickly reach a size refuge from blennies as they grow (Lubchenco 1983, Briggs et al 2018.…”
Section: Microhabitats Enhance Propagule Survivalmentioning
confidence: 69%
“…To date, studies investigating spatial and temporal variation in rates of herbivory on coral reef macroalgae have primarily focused on the consumption of adult thalli (Hay 1981, Lewis 1986, Loffler et al 2015), yet it is often assumed that macroalgal biomass is largely Microhabitats enhance propagule survival controlled through the grazing of early life stages of macroalgae (Done 1992, Diaz-Pulido & McCook 2003, Bellwood et al 2004. Spatial and temporal refuges may facilitate the early post-settlement survival of macroalgae by providing a refuge from herbivory through reductions in grazing pressure (Brandl et al 2014, Brandl & Bellwood 2016, potentially allowing propagules to grow to a size more resistant to grazing (Lubchenco 1983, Stiger et al 2004, Briggs et al 2018. In this study, therefore, we investigate how reef microtopography (i.e., crevices) influences the recruitment, growth and survival of propagules of the common tropical macroalga Sargassum swartzii.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the association with the unpalatable Galaxaura may provide a refuge from herbivory for certain palatable algae [40,59,60], and facilitate their establishment on the reef, increasing macroalgae biodiversity [61]. The facilitation of harmful, allelopathic algal types could decrease the resilience and promote alternative stable states on coral reefs [62]. Some of the identified G .…”
Section: Discussionmentioning
confidence: 99%